Arrhythmias: Modern Classification and Treatment Strategies - Qovulova Nurizar Mo’min qizi (Zien Journals, 2025)
Cardiac arrhythmias are disorders of heart rhythm caused by abnormalities in the generation or conduction n of electrical impulses . These conditions range from benign to life-threatening and can significantly impact patient morbidity and mortality . This article explores modern classification systems for arrhythmias , current diagnostic methods and recent advancements in treatment strategies , including pharmacological therapy , catheter ablation and implantable devices
Keywords: arrhythmia; atrial fibrillation; ventricular tachycardia; bradyarrhythmia